Inelastic Behavior of Materials and Structures Under Monotonic and Cyclic Loading - Altenbach, Holm.; Brünig, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents studies on the inelastic behavior of materials and structures under monotonic and cyclic loads. It focuses on the description of new effects like purely thermal cycles or cases of non-trivial damages. The various models are based on different approaches and methods and scaling aspects are taken into account. In addition to purely phenomenological models, the book also presents mechanisms-based approaches. It includes contributions written by leading authors from a host of different countries.
Creep Behavior Modeling of Polyoxymethylene (POM) Applying Rheological Models -- Experiments and Numerical Simulations on Stress-State-Dependence of Ductile Damage Criteria -- Constitutive Modeling of Dissipative Phenomena in Austenitic Metastable Steels at Cryogenic Temperatures -- Modeling of Continuous Damage Deactivation Accompanying Low Cycle Fatigue of Al-2024 Under Complex Loading -- Computational Multiscale Modeling of Nickel-based Superalloys Containing Gamma-Gamma’ Precipitates -- Homogenized Elastic-Viscoplastic Behavior of Thick Perforated Plates with Pore Pressure -- Experimental and Numerical Investigations of the Effects Associated to Complex Loading Combinations -- Fracture of Cortical Bone Tissue -- A Nonlocal Model of Plasticity and Damage with Different Internal Lengths -- Hysteresis Loop Analysis in Cyclically Strained Materials -- Creep, Plasticity and Fatigue of Single Crystal Superalloys: Physics-Based Life Prediction for Turbine Components in Severe Operating Environments -- Ratchetting of Snake Skin: Experiments and Viscoelastic-plastic Constitutive Model.
Keywords: Mechanics; Mechanics, Applied; Materials science; Building materials; Solid Mechanics; Characterization and Evaluation of Materials; Building Materials